Enhanced recovery after surgery protocols improve time to return to intended oncology treatment following interval cytoreductive surgery for advanced gynecologic cancers. Issue 8 (15th April 2021) - Tankou, Joan Isabelle; Foley, Olivia; Falzone, Michele; Kalyanaraman, Rajeshwari; Elias, Kevin M
Abstract : Objective: The objective of this study was to determine whether the implementation of an enhanced recovery after surgery (ERAS) protocol is associated with earlier return to intended oncology treatment following interval cytoreductive surgery for advanced gynecologic cancers. Methods: Participants comprised consecutive patients (n=278) with a preoperative diagnosis of stage IIIC or IV ovarian cancer, divided into those that received treatment before versus after implementation of an ERAS protocol at our institution. All patients received at least three cycles of neoadjuvant chemotherapy with a platinum based regimen and underwent interval cytoreduction via laparotomy with the intent to deliver additional cycles of chemotherapy postoperatively. The primary outcome was defined as the timely return to intended oncologic treatment, defined as the percentage of patients initiating adjuvant chemotherapy within 28 days postoperatively. Results: The study cohorts included 150 pre-ERAS patients and 128 post-ERAS patients. Median age was 65 years (range 58–71). Most patients (211; 75.9%) had an American Society of Anesthesiologists score of 3, and the median operative time was 174 min (range 137–219). Median length of stay was 4 days (range 3–5 days) in the pre-ERAS cohort versus 3 days (range 3–4) in the post-ERAS cohort (p<0.0001). At 28 days after operation, 80% of patients had resumed chemotherapy in the post-ERAS cohort compared with 64% in the pre-ERAS cohort (odds ratio (OR) 2.29, 95% confidence interval (CI) 1.36 to 3.84; p=0.002). In multivariate logistic regression analysis, the ERAS protocol was the strongest predictor of timely return to intended oncology treatment (OR 10.18, 95% CI 5.35 to 20.32). Conclusion: An ERAS protocol for gynecologic oncology patients undergoing interval cytoreductive surgery is associated with earlier resumption of adjuvant chemotherapy.